DIFFERENCES IN SCORING OF THORACIC PHOTOGRAPHS BETWEEN MDR-TB AND DS-TB PATIENTS WITH PULMONARY TUBERCULOSIS - Tridharmadi, Epriyanto; Wahyuni Widoretno, Elisabeth Tri; Tahalele, Paul L; M. Nahak, Belinda Peregrina (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Tuberculosis (TB) is ranked as the second deadliest infectious disease in the world. There is a drastic increase in TB cases by 2023 with 92% of these cases being pulmonary TB infections. Thoracic photography is a standard examination performed to determine the development of tuberculosis disease through reviewing populations with TB risk factors, one of which is patients with MDR-TB (Multi-Drug Resistance) can result in increased opacity in the lower lung lobes with pulmonary, cavity, and parenchymal lesions. Thoracic photo scoring was performed to determine the severity of lesions in the thoracic photo images of TB patients with MDR (Multi-Drug Resistance) and DS (Drug-Sensitive).Objective: to compare the scoring of thoracic photographs between of TB patients with MDR-TB and DS-TB.Method: using observational analytic method with cross-sectional research design. The sampling technique used purposive sampling method through medical records with analysis using two tests, namely Wilcoxon and Mann-Whitney comparative test. Radiologic findings that we analyzed were infiltrate, consolidation, cavity, ground glass opacity, fibrosis, bronchiectasis, calcification, node, atelectasis, bullae, emphysema, and other nonlung parenchymal findings.Results: The samples to be analyzed were 55 samples had completed anti-tuberculosis therapy in the 6th month and had thoracic photographs. The Wilcoxon Comparative Test on two paired groups showed a significant difference between the TB group with MDR (p=0.008) and DS (p=0.000). In the Mann-Whitney comparative test on two unpaired groups, there were no significant results either TB groups with MDR and DS (p=0.282). Scoring results in MDR-TB patients after therapy showed mild (3.70%), moderate (44.44%), severe (51.85%) categories. In DS-TB patients, showed mild (37.03%), moderate (48.15%), severe (14.81%) categories.Conclusion: There is a significant difference between the severity of thoracic photographs in TB patients with MDR and without MDR (Drug-Sensitive).